Sponge community (Porifera) in coral reef ecosystem in Sabang, Aceh Province, Indonesia - Elsa Dianita Aulia; Tri Aryono Hadi; Rizkie Satria Utama (Society for Indonesian Biodiversity, 2021)
Abstract. Aulia ED, Hadi TA, Utama RS. 2021. Sponge community (Porifera) in coral reef ecosystem in Sabang, Aceh Province, Indonesia. Biodiversitas 22: 3394-3402. Sponges are one of the most influential benthic organisms in coral reef ecosystems. Many studies about sponge communities have been carried out globally, from tropical to temperate regions. In Indonesia, however, sponge communities have not been adequately observed, especially their diversity and interaction with habitats. Sabang, a developing city located in the northwest of Indonesia, has a lack of information about benthic communities and no reports about sponges. This study investigated the sponge community (species richness, coverage, and morphological characters) and the interactions, both within sponges and with corals and substrates, in Sabang. The study found that the sponge richness (species and morphology) and coverage are categorized as poor, having only 24 species with seven morphologies, and coverage of 1.79 ± 1.03% (SE). The interaction analyses showed significant relationships occur among sponge variables but not between sponges and corals, nor between sponges and their substrates. These results could be attributed to the hydrodynamic-related stresses in Sabang, which are likely influenced by exposure to the open ocean, a condition that is less favorable to diversity and interaction. It is necessary to regularly monitor the condition of benthic communities in Sabang in order to better understand their stable state and detect any change over time.